2021
DOI: 10.1371/journal.pcbi.1009279
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating accidental deviations to minimize generalization error and maximize replicability: Applications in connectomics and genomics

Abstract: Replicability, the ability to replicate scientific findings, is a prerequisite for scientific discovery and clinical utility. Troublingly, we are in the midst of a replicability crisis. A key to replicability is that multiple measurements of the same item (e.g., experimental sample or clinical participant) under fixed experimental constraints are relatively similar to one another. Thus, statistics that quantify the relative contributions of accidental deviations—such as measurement error—as compared to systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…The ability to reliably encode the presence of EB was first quantified based on within-class vs. across-class correlation by counting the proportion of trials where within-class correlation was higher than across-class ( Bridgeford et al, 2021 ). This indicated that M/T cells from anaesthetised mice showed better discriminability initially, but later, M/T cells in the behaving mice performed as well as the anaesthetised mice ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…The ability to reliably encode the presence of EB was first quantified based on within-class vs. across-class correlation by counting the proportion of trials where within-class correlation was higher than across-class ( Bridgeford et al, 2021 ). This indicated that M/T cells from anaesthetised mice showed better discriminability initially, but later, M/T cells in the behaving mice performed as well as the anaesthetised mice ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…The ability to reliably encode the presence of ethyl butyrate was first quantified based on within-class vs. across-class correlation, by counting the proportion of trials where within-class correlation was higher than across-class (Bridgeford et al, 2021). This indicated that M/T cells from anaesthetised mice showed better discriminability initially, but later, M/T cells in the behaving mice performed as well as the anaesthetised mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Discriminability index based on correlation coefficient was calculated in the same way as Dicr , described in (Bridgeford et al, 2021), except that the distance measure used was 1 – Pearson’s correlation coefficient, instead of the Euclidian distance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently proposed method, named discriminability, defined as the fraction of frequency at which the similarity across-subject measurements is smaller than similarity within-subject measurements, can assess the reliability of multivariate data more flexibly and be used to any stage of data processing (Wang et al ., 2020 ). This method is based on nonparametric energy statistics (Rizzo and Székely, 2016 ) and kernel mean embeddings (Muandet et al ., 2016 ) approaches, and it is equivalent to ICC under the Gaussian assumption for univariate data (Wang et al ., 2020 ; Bridgeford et al ., 2021 ; Milham et al ., 2021 ). Methods of data collection and analysis can contribute to low reliability in neuroimaging studies.…”
Section: Methodsmentioning
confidence: 99%